Regulasi Transaksi Finance Technology Dalam Hukum Positif Dan Hukum Islam - Endang Madali; Mohammad Fazri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research discusses finance technology, which is the use of technology to provide better services in finance or banking. This service will certainly facilitate consumers, so that it will grow, and eventually produce a separate industry whose products work with commodities of various conventional financial institutions. The research was conducted using a descriptive qualitative method, with a normative legal research approach, namely a statute approach, conceptual approach, and comparative approach. The aim is to ensure that there are regulations related to Fintech-based financial institutions that are protected by law, both in terms of Positive Law and guidelines for legal provisions that lead to halal either in terms of sharia or Islamic law.